Maintaining musculoskeletal health using a behavioural therapy approach: a population-based randomised controlled trial (the MAmMOTH Study). Issue 7 (1st February 2021) - Macfarlane, Gary J; Beasley, Marcus; Scott, Neil; Chong, Huey; McNamee, Paul; McBeth, John; Basu, Neil; Hannaford, Philip C; Jones, Gareth T; Keeley, Phil; Prescott, Gordon J; Lovell, Karina
Abstract : Objective: Cognitive–behavioural therapy (CBT) has been shown to be effective in the management of chronic widespread pain (CWP); we now test whether it can prevent onset among adults at high risk. Methods: A population-based randomised controlled prevention trial, with recruitment through UK general practices. A mailed screening questionnaire identified adults at high risk of CWP. Participants received either usual care (UC) or a short course of telephone CBT (tCBT). The primary outcome was CWP onset at 12 months assessed by mailed questionnaire. There were seven secondary outcomes including quality of life (EuroQol Questionnaire-five dimensions-five levels/EQ-5D-5L) used as part of a health economic assessment. Results: 996 participants were randomised and included in the intention-to-treat analysis of which 825 provided primary outcome data. The median age of participants was 59 years; 59% were women. At 12 months there was no difference in the onset of CWP (tCBT: 18.0% vs UC: 17.5%; OR 1.05; 95% CI 0.75 to 1.48). Participants who received tCBT were more likely to report better quality of life (EQ-5D-5L utility score mean difference 0.024 (95% CI 0.009 to 0.040)); and had 0.023 (95% CI 0.007 to 0.039) more quality-adjusted life-years at an additional cost of £42.30 (95% CI −£451.19 to £597.90), yielding an incremental cost-effectiveness ratio of £1828. Most secondary outcomes showed significant benefit for the intervention. Conclusions: A short course of tCBT did not prevent onset of CWP in adults at high risk, but improved quality of life and was cost-effective. A low-cost, short-duration intervention benefits persons at risk of CWP. Trial registration number: ClinicalTrials.gov Registry (NCT02668003 ).